Two Tribes - Bowen Cohen, Emily; Pien, Lark; HarperCollins (Firm) (New York, NY, 2023)
"Mia is still getting used to living with her mom and stepfather, and to the new role their Jewish identity plays in their home. Feeling out of place at home and at her Jewish day school, Mia finds herself thinking more and more about her Muscogee father, who lives with his new family in Oklahoma. Her mother doesnt want to talk about him, but Mia cant help but feel like shes missing a part of herself without him in her life. Soon, Mia makes a plan to use the gifts from her bat mitzvah to take a bus to Oklahoma--without telling her mom--to visit her dad and find the connection to her Muscogee side she knows is just as important as her Jewish side"--
Keywords: Stepfamilies; Juvenile fiction; Creek Indians; Families; Jewish girls; Juvenile fiction; Juvenile fiction; Juvenile fiction; Juvenile fiction; Jewish girls; Comic books, strips, etc; Indigenous peoples; Indigenous peoples; Comic books, strips, etc; Stepfamilies; Comic books, strips, etc; Creek Indians; Comic books, strips, etc; Families; Comic books, strips, etc; Comics (Graphic works); Religious comics; Graphic novels; Domestic comics; Coming-of-age comics